2016
DOI: 10.1002/2016jg003484
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term fertilization alters the relative importance of nitrate reduction pathways in salt marsh sediments

Abstract: Salt marshes provide numerous valuable ecological services. In particular, nitrogen (N) removal in salt marsh sediments alleviates N loading to the coastal ocean. N removal reduces the threat of eutrophication caused by increased N inputs from anthropogenic sources. It is unclear, however, whether chronic nutrient overenrichment alters the capacity of salt marshes to remove anthropogenic N. To assess the effect of nutrient enrichment on N cycling in salt marsh sediments, we examined important N cycle pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 61 publications
5
28
0
Order By: Relevance
“…The diversities of both nirS and nosZ communities were connected to land-use (field% vs. nirS: ρ = 0.97, p < 0.001, nosZ: ρ = 0.45, p = 0.020) as well as sediment quality (LOI vs. nirK: ρ = 0.84, p < 0.001, nosZ: ρ = 0.59, p = 0.002; %C vs. nirK: ρ = 0.58, p = 0.002, nosZ: ρ = 0.91, p < 0.001; %N vs. nirK: ρ = 0.74, p < 0.001, nosZ: ρ = 0.86, p < 0.001; Suppl. Figure 2), and nirS diversity increased with D15 (ρ = 0.44, p = 0.026), agreeing with the previous results on long-term N fertilization increasing both nirS and nosZ diversity (Bowen et al 2013;Kearns et al 2015) and denitrification rates (Peng et al 2016) in salt marsh sediments. The species richness of nirS correlated with the sediment quality (%C: ρ = 0.74, p < 0.001, %N: ρ = 0.56, p = 0.003), and nosZ species richness was positively correlated with peatland proportion (ρ = 0.74, p < 0.001) and related environmental factors (DOC: ρ = 0.86, p < 0.001, NH 4 + : ρ = 0.73, p < 0.001; Suppl.…”
Section: Denitrifying Microbial Communitiessupporting
confidence: 91%
“…The diversities of both nirS and nosZ communities were connected to land-use (field% vs. nirS: ρ = 0.97, p < 0.001, nosZ: ρ = 0.45, p = 0.020) as well as sediment quality (LOI vs. nirK: ρ = 0.84, p < 0.001, nosZ: ρ = 0.59, p = 0.002; %C vs. nirK: ρ = 0.58, p = 0.002, nosZ: ρ = 0.91, p < 0.001; %N vs. nirK: ρ = 0.74, p < 0.001, nosZ: ρ = 0.86, p < 0.001; Suppl. Figure 2), and nirS diversity increased with D15 (ρ = 0.44, p = 0.026), agreeing with the previous results on long-term N fertilization increasing both nirS and nosZ diversity (Bowen et al 2013;Kearns et al 2015) and denitrification rates (Peng et al 2016) in salt marsh sediments. The species richness of nirS correlated with the sediment quality (%C: ρ = 0.74, p < 0.001, %N: ρ = 0.56, p = 0.003), and nosZ species richness was positively correlated with peatland proportion (ρ = 0.74, p < 0.001) and related environmental factors (DOC: ρ = 0.86, p < 0.001, NH 4 + : ρ = 0.73, p < 0.001; Suppl.…”
Section: Denitrifying Microbial Communitiessupporting
confidence: 91%
“…In addition, previous research at our site has demonstrated that fertilization with NO 3 -, which is a strong electron acceptor, has stimulated denitrification (Koop-Jakobsen and Giblin 2010), increased litter respiration (Deegan et al 2012), and decreased soil organic matter stabilization (Mueller et al 2017). Work in another temperate tidal salt marsh, the Great Sippewisset Marsh, has demonstrated that N enrichment can alter the active soil microbial community to favor denitrifying bacteria (Peng et al 2016) and increase R eco (Martin et al 2018). Nonetheless, temporal changes in AGB ( Figure 2) and higher foliar N content (Deegan et al 2012) suggest that some fraction of increased R eco may be attributable to higher maintenance respiration of N enriched S. alterniflora (Hymus et al 2003).…”
Section: Discussionmentioning
confidence: 66%
“…NO 3 − can similarly stimulate primary production (Mallin, Paerl, and Rudek 1991;Mallin et al 1993;Mendelssohn 1979), theoretically increasing NEE and GPP. However, NO 3 − is also a powerful electron acceptor and can stimulate anaerobic bacteria (Giblin et al 2013;Peng et al 2016), thereby also increasing ecosystem respiration (R eco ) (Wigand et al 2014). We are aware of no studies evaluating how ecosystem level NO 3 − enrichment may stimulate R eco to influence ecosystem carbon processes.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon quality and water residence times are thought to regulate denitrification rates globally (Seitzinger et al ; Taylor and Townsend ) and explain between‐estuaries differences in biological N 2 production (Eyre and Ferguson ; Eyre et al ). Increased DIN availability may also accelerate biological N removal by energetically favoring denitrification/ anammox over “conversion” processes like nitrification (autotrophic oxidation of NH 4 + to NO 3 − ) and heterotrophic dissimilatory reduction of NO 3 − to NH 4 + (DNRA) (Peng et al ). The fate of excess N in estuaries therefore depends on the system's limits on both biological growth (assimilatory removal) and microbial N 2 production (dissimilatory removal).…”
mentioning
confidence: 99%